ВИЗНАЧЕННЯ КОЕФІЦІЄНТА НЕСИНУСОЇДАЛЬНОСТІ ФАЗНИХ НАПРУГ З ВИКОРИСТАННЯМ ТРИФАЗНИХ ФІЛЬТРІВ СИМЕТРИЧНИХ СКЛАДОВИХ - Маков, Д.К.; Поліщук, О.В. (Інститут електродинаміки НАН України, Київ, 2016)
The method for measurement of nonsinusoidal factor of phase and line voltages using the converter of single-phase voltage in threephase symmetric system of is developed. Such system of voltages is connected on an input of symmetric components filters (SCF) connected in cascade of negative and positive phase-sequence voltages and matching networks of type US1-3. Simulation and study of dynamic properties of the devices that implement the proposed method, showed that at fast connection of positive phase-sequence voltages the transient decays for a time less than one and a half period of voltage of a fundamental frequency. References 11, table 1, figures 2.